2010
DOI: 10.1152/ajpregu.00797.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of skeletal muscle regeneration by CCR2-activating chemokines is directly related to macrophage recruitment

Abstract: Muscle regeneration requires CC chemokine receptor 2 (CCR2) expression on bone marrow-derived cells; macrophages are a prominent CCR2-expressing cell in this process. CCR2-/- mice have severe impairments in angiogenesis, macrophage recruitment, and skeletal muscle regeneration following cardiotoxin (CTX)-induced injury. However, multiple chemokines activate CCR2, including monocyte chemotactic proteins (MCP)-1, -3, and -5. We hypothesized that MCP-1 is the chemokine ligand that mediates the impairments present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
140
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(154 citation statements)
references
References 39 publications
12
140
0
1
Order By: Relevance
“…Our results suggest that macrophages, a key element in muscle regeneration (8,12,13,16,60,61) known to deliver antiapoptotic and survival signals in other tissues (90)(91)(92)(93)(94)(95)(96), orchestrate the survival and eventually the differentiation of transplanted mesoangioblasts. This suggests that selective modulation of the function of endogenous macrophages could represent an additional strategy to increase the efficacy of stem cell transplantation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results suggest that macrophages, a key element in muscle regeneration (8,12,13,16,60,61) known to deliver antiapoptotic and survival signals in other tissues (90)(91)(92)(93)(94)(95)(96), orchestrate the survival and eventually the differentiation of transplanted mesoangioblasts. This suggests that selective modulation of the function of endogenous macrophages could represent an additional strategy to increase the efficacy of stem cell transplantation.…”
Section: Discussionmentioning
confidence: 74%
“…Macrophages are the best characterized inflammatory cells in the injured muscle (2,3), and in vivo studies have shown that they play an active role in the tissue repair process (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Macrophages dispose of apoptotic myofiber remnants and of debris, produce signals involved in matrix remodeling and neovessel formation, and regulate the activation, proliferation, and differentiation of muscle stem cells.…”
mentioning
confidence: 99%
“…After injection with anti-CCL2, which blocks the interaction with its receptor CCR2, the mice addressed poor functional recovery (43). Disruption of CCL2/CCR2 sig- naling showed markedly reduced invasion of MPs into the injury site and impaired repair of acute skeletal muscle injury (13,14,44). The transplantation of bone marrow from WT mice restored the muscle inflammation and reversed the defects in muscle regeneration of CCR2 2/2 mice (45).…”
Section: Discussionmentioning
confidence: 99%
“…The best-characterized chemokine released by injured muscle is CCL2/MCP-1 [chemokine (C-C motif) ligand 2/monocyte chemoattractant protein-1], which has an important function in initiating and maintaining the inflammatory phase of various types of muscle injury that precedes muscle regeneration (11). Mice deficient in CCR2 [chemokine (C-C motif) receptor 2] have severely impaired monocyte infiltration (whereas the migration of neutrophils and lymphocytes is normal) along with halted angiogenesis, muscle regeneration, and accumulation of pockets of adipocytes at the site of toxin-induced muscle injury (81). Intriguingly, muscle regeneration is completely restored when CCR2-null mice receive bone marrow transplantation from wild-type mice, suggesting that CCL2 release from the muscle mobilizes monocytes directly from the bone marrow (140).…”
Section: Molecular Aspects Of Skeletal Muscle Inflammationmentioning
confidence: 99%
“…On the other hand, mice deficient in the CCR2 ligand, CCL2 have a milder defect in muscle regeneration following toxininduced muscle injury compared with CCR2-null mice (81), suggesting that CCL2 is not essential and that other CCR2 ligands such as CCL7 and CCL12 or other small molecules could participate in mediating immune cell attraction during muscle regeneration (73,140). Nevertheless, monocyte infiltration requires CCL2 expression in the bone marrow, circulating monocytes, and injured muscle fibers (73).…”
Section: Molecular Aspects Of Skeletal Muscle Inflammationmentioning
confidence: 99%